Controlled-Phase Gate Using Dynamically Coupled Cavities and Optical Nonlinearities - Heuck, Mikkel; Jacobs, Kurt; Englund, Dirk R. (Physical review letters, 2020)
We show that relatively simple integrated photonic circuits have the potential to realize a high fidelity deterministic controlled-phase gate between photonic qubits using bulk optical nonlinearities. The gate is enabled by converting travelling continuous-mode photons into stationary cavity modes using strong classical control fields that dynamically change the effective cavity-waveguide coupling rate. This architecture succeeds because it reduces the wave packet distortions that otherwise accompany the action of optical nonlinearities [J. Shapiro, Phys. Rev. A 73, 062305 (2006)PLRAAN1050-294710.1103/PhysRevA.73.062305; J. Gea-Banacloche, Phys. Rev. A 81, 043823 (2010)PLRAAN1050-294710.1103/PhysRevA.81.043823]. We show that high-fidelity gates can be achieved with self-phase modulation in χ^{(3)} materials as well as second-harmonic generation in χ^{(2)} materials. The gate fidelity asymptotically approaches unity with increasing storage time for an incident photon wave packet with fixed duration. We also show that dynamically coupled cavities enable a trade-off between errors due to loss and wave packet distortion. Our proposed architecture represents a new approach to practical implementation of quantum gates that is room-temperature compatible and only relies on components that have been individually demonstrated.